Development of Sensory-Rich Teaching Materials for Learners with Special Needs - Ocate, Jane; Layona, Shirley (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study focused on the development, validity, and acceptability of sensory-rich teaching materials for learners with special needs in inclusive educational settings in Aranyaprathet, Sa Keo Province, Thailand. Anchored on the ADDER Model, Multisensory Learning Theory, Sensory Integration Theory, and Constructivist Learning Theory, the study aimed to identify learners’ sensory needs in terms of visual stimulation, auditory stimulation, tactile engagement, and kinesthetic activities and to develop instructional materials responsive to these needs. The study utilized descriptive-survey and Research and Development (R&D) methods. Respondents included selected special education and general education teachers, as well as evaluators composed of special education teachers, inclusive education teachers, and school administrators. Researcher-made questionnaire-checklists and evaluators’ assessment checklists were used as instruments, while frequency counts, percentages, and means were employed in data analysis through SPSS. Findings revealed that learners with special needs demonstrated very high needs for visual, auditory, tactile, and kinesthetic sensory stimulation, with visual stimulation obtaining the highest overall mean. The developed sensory-rich teaching materials were evaluated as very highly valid in terms of content and pedagogical validity, sensory and instructional design, technical, physical and safety quality, and usability and contextual relevance. Likewise, the materials were rated very highly acceptable in terms of sensory modality, pedagogical efficacy and design, usability and safety, and learner engagement and affective response. The study concluded that sensory-rich instructional materials are highly appropriate for inclusive and special education settings because they support learner engagement, participation, accessibility, and multisensory learning experiences. The study recommended the wider utilization and validation of sensory-rich materials and encouraged future studies to determine their effectiveness in improving academic and developmental outcomes. The study supports Sustainable Development Goal (SDG) 4 on Quality Education by promoting inclusive and accessible learning opportunities for learners with special needs. It also aligns with SDG 10 on Reduced Inequalities through the promotion of equitable educational participation and inclusive instructional practices. The study contributes to educational and institutional sustainability by encouraging adaptive, learner-centered, and inclusive teaching approaches that improve long-term accessibility and participation in education. It also supports community sustainability by strengthening collaboration among teachers, schools, parents, and educational stakeholders in creating supportive learning environments for learners with special needs.